Absolute protein assay for the simultaneous quantification of two epoxide hydrolases in rats by mass spectrometry–based targeted proteomics. Issue 14 (12th June 2021) - Wu, Ting; Xi, Xiaoyun; Chen, Ying; Jiang, Chao; Zhang, Qian; Dai, Guoliang; Bai, Yongtao; Zhang, Weidong; Ni, Ting; Zou, Jiandong; Ju, Wenzheng; Xu, Meijuan
Abstract: Epoxide hydrolases catalyze the hydrolysis of both exogenous and endogenous epoxides to the corresponding vicinal diols by adding water. Microsomal and soluble epoxide hydrolase are two main mammalian enzymes that have been intensely characterized. The purpose of this investigation was to develop and validate a proteomics assay allowing the simultaneous quantification of microsomal and soluble epoxide hydrolase in rats. Protein quantification was realized through targeted proteomics using liquid chromatography with tandem mass spectrometry for the determination of trypsin‐specific surrogate peptides after digestion. Stable isotope‐labeled peptides were used as the internal standards. The chromatography of the surrogate peptides was performed on an Agilent SB C18 column (100 mm × 4.6 mm, 1.8 µm) with gradient elution. Acetonitrile containing 0.1% formic acid and 0.1% formic acid aqueous solution were used as mobile phases. A multiple reaction monitoring method in a positive ionization mode was used for the simultaneous detection of the peptides. The method was validated concerning the specificity, linearity, within‐day and between‐day accuracy and precision, matrix effect, stability, and digestion efficiency. The developed assay was successfully used to quantify the protein levels of microsomal and soluble epoxide hydrolase in rat liver, kidney, and heart S9 samples.